Anomalous outbreaks of an invasive defoliator and native bark beetle facilitated by warm temperatures, changes in precipitation and interspecific interactions. Issue 5 (26th February 2019) - Ward, Samuel F.; Aukema, Brian H.
Abstract : Biotic disturbance agents such as insects can be highly responsive to climatic change and have widespread ecological and economic impacts on forests. Quantifying the responses of introduced and native insects to climate, including how dynamics of one agent may mediate those of another, is important for forecasting disturbance and associated impacts on forest structure and function. We investigated drivers of outbreaks by larch casebearer Coleophora laricella, an invasive defoliator, and eastern larch beetle Dendroctonus simplex, a native, tree‐killing bark beetle, on tamarack Larix laricina from 2000 to in Minnesota, USA. We evaluated the utility of temporal, spatial and climatic variables in predicting the presence/absence of outbreaks of each insect in cells of rasterized aerial survey data. The role of defoliation by larch casebearer in outbreaks of eastern larch beetle was also investigated. For both species, the most important predictors of outbreak occurrence were proximity of conspecific outbreaks in space and time. For larch casebearer, outbreak occurrence was positively associated with spring precipitation and warmer growing seasons. Outbreak occurrence of eastern larch beetle was positively associated with warmer and dryer years and was more likely in cells with prior defoliation by larch casebearer. Our results demonstrate that climate can drive large scale outbreaks of introduced and non‐native disturbance agents on a single host species, and that interactions at the tree level between such agents may scale up to manifest across large temporal and spatial scales.